2008
DOI: 10.1007/s00439-008-0595-4
|View full text |Cite
|
Sign up to set email alerts
|

The association of SNPs in ADIPOQ, ADIPOR1, and ADIPOR2 with insulin sensitivity in a cohort of adolescents and their parents

Abstract: Few studies have examined the association of SNPs in the adiponectin (ADIPOQ) and adiponectin receptor 1 and 2 (ADIPOR1, ADIPOR2) genes with the euglycemic clamp, i.e. the gold standard measure of insulin sensitivity. The association of comprehensive tag SNPs in these genes with insulin sensitivity was examined in a cohort of adolescents and their parents. Probands and siblings (n = 441, mean age = 17.9 years) were recruited along with their parents (n = 262, mean age = 47.9 years).Typed SNPs included 21 SNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The adiponectin gene resides within the susceptibility loci for T2DM and insulin resistance syndrome on chromosome 3q27 (Kissebah et al, 2000;Vionnet et al, 2000). Accordingly, several SNPs have been described in the adiponectin gene and are associated with metabolic phenotypes including obesity, T2DM and insulin resistance (Stumvoll et al, 2002;Bouatia-Naji et al, 2006;Hara et al, 2002;Hivert et al, 2008;Tso et al, 2006;Schwarz et al, 2006;Szopa et al, 2009;Jang et al, 2008;Pérez-Martínez et al, 2008;Rasmussen-Torvik et al, 2009;Melistas et al, 2009). Among all, T45G and G276T SNPs of adiponectin gene are widely studied in relation to their associations with the metabolic phenotypes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The adiponectin gene resides within the susceptibility loci for T2DM and insulin resistance syndrome on chromosome 3q27 (Kissebah et al, 2000;Vionnet et al, 2000). Accordingly, several SNPs have been described in the adiponectin gene and are associated with metabolic phenotypes including obesity, T2DM and insulin resistance (Stumvoll et al, 2002;Bouatia-Naji et al, 2006;Hara et al, 2002;Hivert et al, 2008;Tso et al, 2006;Schwarz et al, 2006;Szopa et al, 2009;Jang et al, 2008;Pérez-Martínez et al, 2008;Rasmussen-Torvik et al, 2009;Melistas et al, 2009). Among all, T45G and G276T SNPs of adiponectin gene are widely studied in relation to their associations with the metabolic phenotypes.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with the association at protein levels, genetic studies have also demonstrated a link between adiponectin gene and the metabolic phenotypes. Several single nucleotide polymorphisms (SNPs) are described in the adiponectin gene and were found to be associated with obesity (Stumvoll et al, 2002;BouatiaNaji et al, 2006), type 2 diabetes mellitus Hivert et al, 2008;Tso et al, 2006;Schwarz et al, 2006;Szopa et al, 2009) and insulin resistance (Stumvoll et al, 2002;Jang et al, 2008;Pérez-Martínez et al, 2008;Rasmussen-Torvik et al, 2009;Melistas et al, 2009). Although it should be noted that other studies have reported a lack of such an association; with conflicting reports observed, at times, within the same ethnicity (Lee et al, 2005;Vasseur et al, 2002;Populaire et al, 2003;Gu et al, 2004;Vozarova de Courten et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Ramya et al [24] conducted a study in the a South Indian population and found a genetic association of rs822393 (-4522 C/T) variants of the adiponectin gene with type 2 diabetes mellitus (T2DM), obesity, and the serum adiponectin level. Rasmussen-Torvik et al [25] suggested that rs822393 was significantly associated with insulin sensitivity in white subjects. Wassel et al [26] indicated that ADIPOQ SNP rs822393 was strongly associated with serum adiponectin concentrations in white subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Adiponectin is secreted and present in plasma in various multimeric forms, for which the biological significance remains to be determined. Rasmussen-Torvik et al (5) showed that binding of adiponectin to adiponectin receptors (ADIPOR1 and ADIPOR2) in mice results in increased AMP-activated protein kinase activity and peroxisome proliferator–activated receptor-α activity. In humans, both receptors are expressed mainly in skeletal muscle and adiponectin could thus play a role in energy metabolism.…”
mentioning
confidence: 99%
“…Furthermore, it is not known whether the genetics of plasma adiponectin overlap with the genetics of body weight and insulin sensitivity/diabetes or other individual components of the metabolic syndrome. Several studies showed convincing association of genetic variants near and in the promoter region of the ADIPOQ gene with plasma adiponectin and type 2 diabetes or type 2 diabetes–related traits (5,9,10). …”
mentioning
confidence: 99%